2010
DOI: 10.1111/j.1440-1681.2010.05353.x
|View full text |Cite
|
Sign up to set email alerts
|

ZJM‐289, a novel nitric oxide donor, alleviates the cerebral ischaemic–reperfusion injury in rats

Abstract: 1. Current studies indicate that nitric oxide (NO) plays a dual role as both a protective and pathogenic factor in focal cerebral ischaemia depending on the level, location, source and environment. The present study hypothesized that the NO donor ZJM-289 could inhibit cerebral ischaemia-reperfusion (I/R) injury and investigated the mechanism of the beneficial events. 2. Adult male rats were randomly divided into four groups: (i) sham operated; (ii) I/R (ischaemia for 90 min and reperfusion for 24 h) treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Absence of CSE or CAT/3-MST aggravates ischemic brain injury (Zheng et al, 2015). Many preclinical studies revealed that exogenous NO donors (e.g., SNP, sydnonomines, NONOates, and NO-NBP) and H 2 S donors (e.g., NaSH, ADTOH, and H 2 S-NBP) are beneficial in ischemic stroke (Willmot et al, 2005; Zhuang et al, 2010; Wang X. et al, 2014; Wang Y. et al, 2014). In this study, we firstly performed both in vivo and in vitro experiments to explore whether NOSH-NBP, in comparison with the single-donors, i.e., NO-NBP and H 2 S-NBP, have therapeutic effects on ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Absence of CSE or CAT/3-MST aggravates ischemic brain injury (Zheng et al, 2015). Many preclinical studies revealed that exogenous NO donors (e.g., SNP, sydnonomines, NONOates, and NO-NBP) and H 2 S donors (e.g., NaSH, ADTOH, and H 2 S-NBP) are beneficial in ischemic stroke (Willmot et al, 2005; Zhuang et al, 2010; Wang X. et al, 2014; Wang Y. et al, 2014). In this study, we firstly performed both in vivo and in vitro experiments to explore whether NOSH-NBP, in comparison with the single-donors, i.e., NO-NBP and H 2 S-NBP, have therapeutic effects on ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated that NO or H 2 S-donor derivatives of NBP, NO-NBP (zjm-289), and H 2 S-NBP (8e) exhibit anti-thrombosis, anti-platelet aggregation and neuroprotective properties (Zhuang et al, 2010; Wang X. et al, 2014). NBP was approved by the State Food and Drug Administration (SFDA) of China as a new anti-ischemic drug for stroke in 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Fifthly, NO donors can reduce thrombosis, as in microvessels. And last, in addition to increases in blood levels of NO, other potentially beneficial biochemical changes may occur, as seen experimentally and including increases in endothelial nitric oxide synthase (NOS) and cyclic guanosine monophosphate and reductions in neuronal NOS, nitrotyrosine, and adhesion molecules [3235]. …”
Section: Discussionmentioning
confidence: 99%
“…In short, it appears that NO activation of the GC-PKG pathway may be deleterious, particularly when it leads to induction of iNOS, and some or most of these deleterious effects may be due to NO itself or its peroxide byproducts driven by iNOS. In support of this hypothesis, the NO donor, ZJM-289, was found to alleviate cerebral ischemic-reperfusion injury through inhibition of neuronal NOS and stimulation of the soluble GC-cGMP pathway [100]. The combination therapy of NO donors and PDE5 inhibitors appears to facilitate neurogenesis, oligodendrogenesis, and angiogenesis after stroke [101].…”
Section: Role Of Cgmp-pdes and Tbimentioning
confidence: 99%